Plasma Citrulline as a Biomarker for Early Diagnosis of Necrotizing Enterocolitis in Preterm Infants - Jawale, Nilima; Prideaux, Mallory; Prasad, Malavika; Miller, Malki; Rastogi, Shantanu; for Maimonides Neonatal Group (American Journal of Perinatology, 2020)
Objective Citrulline synthesized by healthy enterocytes and decreases with injury. This work aimed to study plasma citrulline concentrations (CITs) as a biomarker to differentiate among infants presenting with early nonspecific signs and symptoms of necrotizing enterocolitis (NEC) with those who will develop NEC. Further to study the correlation between posttreatment CIT with time to full feeds (TTFF) and length of stay (LOS).Study Design This is a prospective study which included infants < 32 weeks gestational age (GA) with 9 infants each in Group 1 (stage 2/3 NEC), Group 2 (with stage 1 NEC-like presentation), and Group 3 (healthy GA-matched infants). CIT was measured in Groups 1 and 2 within 24 hours of presentation and again in Group 1 after treatment.Results The three groups were similar in clinical characteristics. Median CIT (µmol/L) in Group 1 (15.4 [interquartile range, IQR: 7.3–18.0]) was lower than Group 2 (22.2 [IQR: 18.3–27.3], p = 0.02) and Group 3 (24.9 [IQR: 19.8–31.9], p = 0.009). Posttreatment CIT in Group 1 did not correlate with TTFF (r = 0.15; p = 0.69) and LOS (r =  − 0.33; p = 0.38).Conclusion CIT was lower in infants with NEC as compared with healthy controls and those infants with nonspecific signs of NEC. CIT after treatment does not correlate with TTFF and LOS.Key Points
Keywords: citrulline; necrotizing enterocolitis; preterm; biomarker; case–control